Self-administered acupressure for knee osteoarthritis in middle-aged and older adults: a pilot randomized controlled trial. Issue 2 (April 2020) - Cheung, Denise Shuk Ting; Yeung, Wing-Fai; Suen, Lorna Kwai-Ping; Chong, Tsz Chung; Ho, Yuan-Shan; Yu, Branda Yee-Man; Chan, Lily Ying-Tung; Chen, Hai-Yong; Lao, Li-Xing
Objective: To test the acceptability and feasibility of self-administered acupressure as an intervention for knee pain among middle-aged and older adults with knee osteoarthritis (KOA). Methods: In this pilot randomized controlled trial, 35 participants with KOA were randomized to receive self-administered acupressure (n = 17, two self-administered acupressure training sessions followed by self-practice for 6 weeks) or knee health education (n = 18, two health education sessions about KOA management followed by self-care for 6 weeks). Current pain intensity (primary outcome) was measured using a Numeric Rating Scale (NRS) at baseline and weeks 1, 2, 4 and 6 (post-intervention). Secondary outcome measures included worst and least pain intensity, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), range of motion (ROM) of the knee joints and Short-Form Six-Dimension (SF-6D) scores for health-related quality of life. Results: Participants in both groups attended all training sessions. In the self-administered acupressure group, all subjects mastered the acupressure technique and passed a consistency check. Both groups showed a decreasing trend in current knee pain intensity measured using NRS post-intervention. A medium between-group effect size (0.40) was found, but between-group differences were not statistically significant. The other secondary outcome measures were also comparable between both groups post-intervention (all p > 0.05). Conclusion: A two-session self-administered acupressure training was acceptable to and feasible in participants with KOA. The data generated allowed for calculation of a sample size for a definitive randomized controlled trial (RCT) to confirm whether self-acupressure is effective for pain management in KOA. Furthermore trials with adequate power and longer follow-up periods are warranted.